TIC na formação inicial: uma visão de futuros professores de dois cursos de licenciatura da UFOPA - RABELO, Neliane Mota (Universidade Federal do Oeste do Pará, 2021)
This work presents considerations about the perception of students related to the use of information and communication technologies (ICT) in university education. The society undergoes significant changes in its different dimensions, which projects a great influence on information and communication technologies (ICT) and, consequently, triggering alternative and innovative communication processes. In particular, education is modernized, mainly due to extremely fast and dynamic technological changes and transformations, thus requiring alternative and creative teaching processes capable of producing satisfactory and meaningful learning for students. In this sense, the objectives of this work are focused on the investigation of future teachers of the Integrated Licentiate Course in Mathematics and Physics - LIMF and Licentiate in Educational Informatics - LIE, Federal University of the West of Pará, in Santarém / PA, future teachers , use (and if they use it) and how they perceive this use demonstrating its importance through the use of ICT aiming their academic formation. Through this conception, it is assumed that it is possible to infer about conceptions and understandings about the use, implementation and operation of technological resources, in undergraduate classes aimed at teaching. The methodological procedures are based on the extraction of information, together with the students of this course, through the application of standardized questionnaires, documentary analysis of the Pedagogical Projects of Courses (PPC), which have repercussions of technological applications focused on the training processes, object of the course. The information obtained, through the mentioned instruments, will be correlated with the study proposal based on the content analysis of Bardin (2011). The sample of participants was composed of 15 apprentices of the LIMF course and 14 apprentices of the LIE course. As for the theoretical basis conveyed to this research, we highlight considerations about the emerging technological paradigm pointed out by Valente (1999, 2018) and Moran (2007, 2015), besides punctuating pertinent considerations to teacher education conceptions, for the technological era, discussed in the works of Kenski (2001, 2003, 2007, 2009, 2012 and 2017); Masetto (1998, 2010, 2013) and Zabalza (2007). The results project different perceptions of the students. Such testimonies envision technological practices that are still far from their reality in the classroom and that, to the teacher, become major challenges still in the present time. There is hope that they may learn less traditionally. They hope that the teacher, by inserting in his classes dynamic forms that facilitate the teaching-learning process, will allow to promote conditions for future teachers in their initial formation to build knowledge about the use of existing technological resources, based on their understandings and who are able to associate them with their teaching practice using available resources, thus becoming a professional that meets the new demands of society.